A case report of X-linked agammaglobulinemia complicated with necrotic pneumonia - Zhang, Xiaoyuan; Zhu, Jianfang (Translational Pediatrics, 2026)
X-linked agammaglobulinemia (XLA) complicated with necrotic pneumonia caused by Bruton tyrosine kinase (BTK) gene variation was reported. Clinical features and treatment were analyzed. In this case, repeated pulmonary infection and necrotizing pneumonia (NP) accompanied by multiple systemic infections were eventually confirmed to be caused by BTK gene defect. After regular treatment with gamma globulin, the symptoms were relieved. This case report aimed to improve clinicians’ understanding of the disease so that diagnosis and treatment can be decided as early as possible, for improving patient’s prognosis.